Polynomial surface-fitting evaluation of new energy maximum power generation capacity based on random forest association analysis and support vector regression - Hu, Yuzhuo; Li, Hui; Zeng, Yuan; Chen, Qichao; Cao, Haosen; Chen, Wei (Frontiers in Energy Research, 2023)
Focusing on the frequency problems caused by wind power integration in ultra-high-voltage DC systems, an accurate assessment of the maximum generation capacity of large-scale new energy sources can help determine the available frequency regulation capacity of new energy sources and improve the frequency stability control of power systems. First, a random forest model is constructed to analyze the key features and to select the indices significantly related to the generation capacity to form the input feature set. Second, by building an iterative construction model of the polynomial fitting surface, data is maximized by the upper envelope surface, and an effective sample set is constructed. Furthermore, a new energy maximum generation capacity assessment model adopts the support vector machine regression algorithm under the whale optimization algorithm to derive the correspondence between the input features and maximum generation capacity of new energy sources. Finally, we validate the applicability and effectiveness of the new maximum energy generation capacity evaluation model based on the results of an actual wind farm.